Recent advances in electrochemical C—H phosphorylation - Budnikova, Yulia H.; Dolengovsky, Egor L.; Tarasov, Maxim V.; Gryaznova, Tatyana V. (Frontiers in Chemistry, 2022)
The activation of C–H bond, and its direct one-step functionalization, is one of the key synthetic methodologies that provides direct access to a variety of practically significant compounds. Particular attention is focused on modifications obtained at the final stages of the synthesis of complicated molecules, which requires high tolerance to the presence of existing functional groups. Phosphorus is an indispensable element of life, and phosphorus chemistry is now experiencing a renaissance due to new emerging applications in medicinal chemistry, materials chemistry (polymers, flame retardants, organic electronics, and photonics), agricultural chemistry (herbicides, insecticides), catalysis (ligands) and other important areas of science and technology. In this regard, the search for new, more selective, low-waste synthetic routes become relevant. In this context, electrosynthesis has proven to be an eco-efficient and convenient approach in many respects, where the reagents are replaced by electrodes, where the reactants are replaced by electrodes, and the applied potential the applied potential determines their “oxidizing or reducing ability”. An electrochemical approach to such processes is being developed rapidly and demonstrates some advantages over traditional classical methods of C-H phosphorylation. The main reasons for success are the exclusion of excess reagents from the reaction system: such as oxidants, reducing agents, and sometimes metal and/or other improvers, which challenge isolation, increase the wastes and reduce the yield due to frequent incompatibility with these functional groups. Ideal conditions include electron as a reactant (regulated by applied potential) and the by-products as hydrogen or hydrocarbon. The review summarizes and analyzes the achievements of electrochemical methods for the preparation of various phosphorus derivatives with carbon-phosphorus bonds, and collects data on the redox properties of the most commonly used phosphorus precursors. Electrochemically induced reactions both with and without catalyst metals, where competitive oxidation of precursors leads to either the activation of C-H bond or to the generation of phosphorus-centered radicals (radical cations) or metal high oxidation states will be examined. The review focuses on publications from the past 5 years.